PENGARUH RASIO LANCAR DAN RASIO UTANG TERHADAP EKUITAS TERHADAP HARGA SAHAM PERUSAHAAN FARMASI TERDAFTAR DI BURSA EFEK INDONESIA - Tri Kurniati; M. Kausar Maulana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research was conducted to determine the effect of the current ratio and debt to equity ratio on stock prices in pharmaceutical companies listed on the Indonesian Stock Exchange. This research method is quantitative analysis. The data used is secondary data frompharmaceutical companies obtained from the Indonesia Stock Exchange. There search data was analyzed regression lenear simultaneously and partially software. Based on the results of simultaneously the current ratio and debt to equity ratio have a positive and significant effect on stock prices, butpartially the current ratio and debt to equity ratio have a negative and significant effect on stock pricesing pharmaceutical companies listed on the Indonesia Stock Exchange.